Functional and Motility Disorders of the Gastrointestinal Tract A Case Study Approach - Lacy, Brian E.; Crowell, Michael D.; DiBaise, John K. (Springer New York : Imprint: Springer, 2015)
This volume covers the myriad of functional and motility gastrointestinal disorders in a comprehensive manner. The book is divided into seven major sections, with each section beginning with a brief case presentation highlighting the specific disorder to be reviewed. Appropriate criteria is highlighted, followed by a brief review on the epidemiology, etiology, pathophysiology, diagnosis and treatment of each specific disorder. Two to three key teaching "pearls", test questions, and key references are also provided for each chapter. The book is organized so that each chapter can stand on its own and be used as a quick reference source in the clinic. Alternatively, it can be read cover to cover as an authoritative textbook on gastrointestinal functional and motility disorders. Written by international experts in the field of motility disorders, Functional and Motility Disorders of the Gastrointestinal Tract: A Case Study Approach is an invaluable resource for experienced physicians, students, residents, fellows, nurse practitioners, and physician assistants.  .